Dos nuevos yacimientos de icnitas de dinosaurios en La Rioja y en la provincia de Soria (España) - Casanovas, Maria Lourdes; Ezquerra, Rubén; Fernández, Arturo; Pérez- Lorente, Felix; Santafe, Jose Vicente; Torcida, Fidel (Coloquios de Paleontología, 1995)
Sin resumen